The Relationship Between Professional Practice and Architectural Education in Turkey - ARSLAN, MEHMET EMRE; Ceylan, Salih (IGI Global, 2024)
One of the biggest challenges in architectural education is its necessity to adapt to a continuously evolving professional environment. In many countries, professional organizations such as chambers of architects and educational institutions work together to come up with various strategies and formulae that strength¬en the bond between the two. However, the rigid system imposed to the higher education institutions in Turkey hinders architecture schools to propose effective strategies for creating such bonds. Historical research on the topic indicates that this bond has become weaker in time. Currently, concerns reflect on the opinions of various stakeholders. As a result, there are various comments on architectural education to become more sufficient for the professional environment. This chapter aims to draw a framework for the relationship between education and practice in Turkey. It elaborates on the past, present and the future of the relationship from local and global perspectives. © 2024, IGI Global. All rights reserved.
Novel Approaches to Urban Design and Architecture Education: Design Studio Practice and Pedagogy